Analysis Of The Business Of Kelor Pleret Crackers In Singojuruh Village, Banyuwangi Regency - Lintang Balgis Humairoh; R. Alamsyah Sutantio; Dinu Saadillah; Aditya Nizar Al Ardi; Aulia Nadhirah (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
Crackers are a food that is very popular with the people of Indonesia. One type of crackers that exist are kelor pleret crackers. Kelor pleret crackers are a type of food made from the basic ingredients of Moringa leaves which are processed through steaming the dough, molding, drying, and frying. This study aims to determine the production process, analyze the business feasibility and marketing mix strategy for the Moringa pleret cracker product. This study uses the BEP (Break Event Point) analysis method, R/C Ratio (Revenue Cost Ratio), and ROI (Return On Investment). 25 packages, while the BEP value (price) is IDR 6,300.32 with a predetermined selling price of IDR 10,000 per package, while the value of the R/C ratio is 1.58 and the ROI value is 9.3%. has been done, it can be said that the kelor pleret cracker business is profitable and can be run.The marketing strategy analysis carried out on the kelor pleret cracker business uses 4P marketing mix analysis (Product, Price, Place, Promotion).The product offered is packaged moringa pleret crackers with a net weight of 100 grams per package Marketing activities for kelor pleret crackers are carried out directly by producers to consumers through social media such as Instagram and Whatsapp.